SENSORY CHARACTERISTICS AND NUTRITIONAL QUALITIES OF PORK SAUSAGE TREATED WITH BOILED â€˜PREKESEâ€™ (TETRAPLEURA TETRAPTERA) POD EXTRACT - Teye, G. A.; Adzitey, F.; Bawah, J.; Boateng, A. B. (UDS International Journal of Development, 2016)
This study was conducted to assess the effect of â€œprekeseâ€ pod extract (PPE) prepared from ground, cut or whole boiled â€˜prekeseâ€™ on the sensory characteristics and nutritional qualities of pork sausages. Four (4) kg of minced pork was obtained and was divided into four batches of 1 kg each. Each batch was spiced and 10 ml of PPE added. These were stuffed into casing and vacuum sealed in transparent polythene bags and refrigerated at 4oC for nutritional and sensory analyses. A five point category scale was used for the sensory analyses. The inclusion of 10 ml of PPE from the various treatments had no effect (P > 0.05) on the acceptability of the sausages. It was also observed from the proximate analysis that, there were no significant differences in the protein content of the products but there were significant differences in terms of moisture, crude fat and the pH. The use of â€˜prekeeseâ€™ pod extract in the preparation of pork sausages had no adverse effect on the sensory attributes of the sausages. â€˜Prekeeseâ€™ pod extract could not improve upon the protein content of the pork sausages. Moisture and pH contents of pork sausages prepared without boiled â€˜prekeseâ€™ was lower than pork sausages prepared using boiled â€˜prekeseâ€™.Â Â Â  Keywords: Boiled â€˜prekeseâ€™, Nutritional qualities, Pork sausage, Sensory characteristicsÂ Â 